Integration of fish culture in hydroponic agriculture in flood-prone areas - Hossain, Md. Shakhawate; Alam, Md. Jahangir (Penerbit Universiti Kebangsaan Malaysia, 2020)
Floating bed organic cultivation of different vegetables, flowers, and seedlings have been shown a promising means of agricultural crop production in different wetland areas of Bangladesh. The present study was aimed at finding out the suitability of the integration of fish in this system in waterlogged areas. The experiment consists of three treatments namely SB, silver barb Barbonymus gonionotus; T, tilapia Oreochromis niloticus; and SBT, tilapia: silver barb (1:1 ratio) with three replications of 6.75 m2 floating vegetable beds in each. Fish were stocked at a rate of 3 m-2 for five months of culture and fed at 1.5% of body weight twice daily. Over the study period, water quality parameters and fish survival rate did not vary significantly among different treatments. Tilapia showed significantly higher daily and specific growth rates in mono- and polyculture, but silver barb only in polyculture system. Thus, total fish production in kg ha-1 was significantly higher in treatments T (p = 0.001) and SBT (p = 0.001) than SB. Vegetable production was not significantly different among treatments. In the financial analysis, the benefit-cost ratio of different treatments was >1, indicating that investment was financially profitable for all treatments, but treatment T and SBT were more profitable. Therefore, we can conclude that integrating fish with floating bed agriculture systems could be an ideal approach to generate alternate income activities and mitigate climate change effects among disaster-prone waterlogged regions of Bangladesh.